Newspaper coverage of tobacco control in New Zealand. (June 2014) - McGee, Rob; Bang, Sophie; Marsh, Louise
Abstract Objective: The New Zealand (NZ) government has proposed that the country be 'Smokefree' by 2025. This paper examines how NZ newspapers have portrayed tobacco control initiatives to achieve this goal. Method: We examined tobacco‐related articles from NZ newspapers published between 1 November 2011 and 31 October 2012, using a coding frame to capture smoking themes, portrayal of actions and degree of support expressed for various pro‐ and anti‐ tobacco control objectives. Results: A total of 537 separate articles were obtained from national and regional newspapers. Six themes appeared in more than 5% of the total articles: Smokefree 2025; smokefree areas; pricing; tobacco industry; plain packaging; and cessation. Overall, articles on tobacco smoking were three times more likely to emphasise actions consonant with tobacco control objectives rather than against them, and to report them with a positive rather than negative tone. Conclusions: NZ tobacco control advocates can take heart from the nature and extent of coverage of tobacco control initiatives. Opportunities for further media advocacy are discussed.